ANALYSIS OF THE ECOSYSTEM OF E-SPORT - Fenyves, László (Studia Mundi – Economica, 2022)
Our daily lives are characterized by constant development, which offers new opportunities for us in several fields of life. As a result of technological development and digitalisation, a new industry (e-sport) has emerged and is growing rapidly. The popularity of e-sport is skyrocketing, but there are still several questions around this issue. Despite or due to the rapid growth, operators, operations, drivers, and contexts of this part of the entertainment industry are still an area that is unknown and needs to be explored. The aim of my research is to explore the current operation of e-sport, understand its characteristics to get a clear picture and provide an overview of the operators in the industry, the correlation between them, and the flow of money and value. To achieve my research goal, I conducted an analysis of the e-sport ecosystem. In the course of secondary data collection, I studied and processed existing domestic and international ecosystem analyses in literature, which I consider to be the most useful and valid for the purpose of the research. There are significant differences between existing ecosystem analyses; some are oversimplified while some are more complex for representation, but as far as I am concerned, none were completely complex. Models presented in this article do not, in my view, provide the most accurate picture of e-sport per se, but provide a comprehensive picture of the industry by integrating the positive aspects and systems of these analyses.
Keywords: e-sport; ecosystem; stakeholders